2020
DOI: 10.1200/jco.19.02044
|View full text |Cite|
|
Sign up to set email alerts
|

EV-101: A Phase I Study of Single-Agent Enfortumab Vedotin in Patients With Nectin-4–Positive Solid Tumors, Including Metastatic Urothelial Carcinoma

Abstract: PURPOSE To assess the safety/tolerability and antitumor activity of enfortumab vedotin (EV), a novel investigational antibody-drug conjugate that delivers the microtubule-disrupting agent, monomethyl auristatin E, to cells that express Nectin-4. METHODS EV-101 is a phase I dose escalation/expansion study that enrolled patients with Nectin-4–expressing solid tumors (eg, metastatic urothelial carcinoma [mUC]) who progressed on ≥ 1 prior chemotherapy regimen and/or programmed death-1 receptor/programmed death lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
149
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(193 citation statements)
references
References 14 publications
3
149
2
Order By: Relevance
“…Of note, patients in the EV-101 study who had previously received ICI therapy had an ORR of 42% (95% CI, 31.2–52.5%). In addition, patients with high tumor burdens such as liver metastases had a 36% (95% CI, 20.4–54.9%) ORR [ 59 ].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…Of note, patients in the EV-101 study who had previously received ICI therapy had an ORR of 42% (95% CI, 31.2–52.5%). In addition, patients with high tumor burdens such as liver metastases had a 36% (95% CI, 20.4–54.9%) ORR [ 59 ].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…EV is an ADC targeting Nectin-4, a cell adhesion molecule highly expressed in nearly all urothelial tumors, conjugated to monomethyl auristatin E, a microtubule-disrupting agent 47 . In the dose expansion portion of the EV-101 trial, 112 mUC patients who failed at least one prior therapy received EV 48 . The confirmed ORR was 43%, including 5% CR, and the median duration of response was 7.4 months.…”
Section: Antibody–drug Conjugatesmentioning
confidence: 99%
“…Patients with metastatic (M1) Urothelial cancer (UC) have an extremely ominous prognosis, with a 5 year survival rate of <5% after receiving cisplatinbased combination chemotherapy [1][2][3]. Thus, it is highly welcome news that within a year, two publications of Phase II (or I-II) trials of novel agents, erdafitinib [4] and enfortumab vedotin (EV) [5], have reported their efficacy and toxicity in patients with previously treated metastatic or unresectable UC. Each report impressive and similar objective response rates (ORRs) including complete responses (CRs) and prolongation of survival in several groups of patients.…”
mentioning
confidence: 99%
“…As opposed to erdafitinib, whose target is only found in a minority of advanced UCs, EV's target, Nectin -4, a trans-membrane immunoglobulin-like protein implicated in cell-cell adhesion [9], and in processes such as immune modulation and host pathogen interactions [9], is expressed by almost all advanced UCs [5,9]. Nectin -4 also has moderate expression in human skin [10][11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation